THE IMPACT OF FIXED CONCENTRATIONS SEDATION INFUSIONS ON FLUID OVERLOAD IN CRITICALLY ILL CHILDREN. Issue 9 (17th August 2016) - Sutherland, Adam; Jemmett, Elizabeth; Playfor, Stephen
Abstract : Introduction: Fluid overload of 10% at 48 hrs (100 ml/kg additional fluid) is strongly associated with morbidity in critically ill children.1 Contributors include fluid resuscitation, acute kidney injury, and administration of intravenous drugs. Acute Kidney Injury has been observed to be more prevalent in infants.2 Drug infusions are historically prepared according to bodyweight to run at large volumes to facilitate end-of-bed calculation and administration. We report the impact of using standardised concentrations on fluid overload in critically ill children in a tertiary general PICU. Methods: Administration of sedation infusions was prospectively documented using purposive sampling until a population-representative sample for age and weight was obtained. Infusion volumes were calculated in ml/kg/day for different weight groups – 0–5 kg, 5–20 kg and <20 kg – and compared with equivalent volumes for weight-based infusions. Results: 33 patients received sedation infusions over a 5 week period. Overall drug volumes were reduced by 50.3%(41.3 to 58.7%) from 5.19 ml/kg to 2.65 ml/kg. Greatest reduction was seen in the smallest patients (total reduction 68% (16.72 ml/kg vs 5.36 ml/kg). Midazolam volumes in patients >20 kg was observed to increase (0.75 ml/kg vs. 0.95 ml/kg) but this did not have an impact on overall fluid burden. Conclusions: Weight based sedation infusions may contribute to fluid overload related morbidity, especially in infants. An infant on morphine and midazolam at standard doses (20 mcg/kg/hr and 90 mcg/kg/hr respectively) will receive 16.7 ml/kg/day (33.4% of critical fluid overload at 48 hrs) when using weight-based infusions. Using standard concentrations reduces this volume to 5.36 ml/kg/day (10.7% of critical fluid overload at 48 hrs).